Reconstructing Arbitration as the Primary Mechanism for Investment Dispute Resolution in Indonesia: Balancing Legal Certainty, Investor Protection, and Judicial Supervision - Imamuddin; Vressilia Witama; M. Rangga Syahputra Saragih; Rayhan Nandini Telaumbanua (ISNU Sumatera Utara, 2026)
Investment plays a pivotal role in promoting economic growth and attracting capital, yet it is inherently vulnerable to disputes arising from contractual disagreements, regulatory changes, and conflicting legal interests. Although arbitration has been widely recognized as an effective mechanism for resolving investment disputes, existing scholarship predominantly emphasizes its procedural advantages while paying limited attention to its broader institutional function within the investment governance system. This study aims to examine the urgency of arbitration in resolving investment disputes in Indonesia and to develop an integrated institutional framework for strengthening arbitration as a mechanism for ensuring legal certainty and investor protection. Employing normative legal research, the study adopts statutory and conceptual approaches by analyzing Law Number 30 of 1999 on Arbitration and Alternative Dispute Resolution, Law Number 25 of 2007 on Investment, the 1958 New York Convention, and relevant legal literature. The findings demonstrate that arbitration provides a legally recognized, final and binding dispute resolution mechanism that enhances procedural efficiency, neutrality, confidentiality, and legal certainty, thereby strengthening investor confidence. However, its effectiveness depends not only on legislative regulation but also on institutional coherence among arbitral tribunals, national courts, and enforcement authorities. Accordingly, this study proposes an Integrated Investment Arbitration Framework, which conceptualizes arbitration as an institutional governance model founded upon four interrelated dimensions: legal certainty, arbitral independence, proportional judicial supervision, and effective enforcement. The study concludes that strengthening these institutional dimensions is essential to maintaining investor confidence, improving Indonesia's investment climate, and aligning domestic arbitration practice with contemporary international legal standards.